Anterior Cruciate Ligament (ACL) Injuries in Soccer: A Comparative Study of Natural Grass and Artificial Turf Playing Surfaces - Abdulla, Shafea; Salama, Aladdin; Kurek, Aleksandra; Kaminskaya, Anhelina; Feretycki, Hubert; Głowacka, Aleksandra; Górecki, Patryk; Ivanchuk, Sofiia; Domińczak, Dominika; Savchak, Tetiana (Quality in Sport, 2026)
Purpose of research: This study considers biomechanical, mechanical, and epidemiological factors that differentiate natural grass (NG) from artificial turf (AT) in relation to anterior cruciate ligament (ACL) injury risk in soccer, with particular emphasis on shoe-surface interactions plus knee kinematics. Research materials and methods: A comprehensive literature review was conducted, incorporating biomechanical studies, epidemiological reports, and meta-analyses published between 2022 and 2025. The analysis used data from large-scale databases, including the NCAA and NEISS, to compare injury incidence across several demographics, playing levels, and exposure types. Basic results: Modern artificial turf exhibits 15% to 22% greater rotational resistance than natural grass, resulting in a hazardous "cleat lock" effect during pivoting maneuvers. Epidemiological data indicate that female players experience up to an 18% higher ACL injury risk on artificial turf, while male cohorts show no significant overall difference during match play. In contrast, injury risks on natural grass primarily result from surface irregularities, such as divots. Conclusions: Artificial turf offers a considerable mechanical risk to the ACL due to increased rotational traction and surface stiffness. Effective risk mitigation calls for a diverse approach, including the enforcement of appropriate footwear (conical studs), consistent surface upkeep to prevent compaction, and the implementation of daily neuromuscular injury prevention programs such as FIFA 11+.